Trade and pricing policies in the context of sustainable livestock production in sub-Saharan Africa - Williams, Timothy O. (International Livestock Centre for Africa, 1993)
This papers examines the trade and price trends for livestock products emerging for the 1990s in sub-Saharan Africa, the issues that these trends present for policy research, the potential impact of research that addresses the identified issues, and wheather ILCA have a comparative advantage in undertaking work on the identified issues and wheather there are potential collaborators to work with. The issues and areas identified constitute a modest set of suggestions for future research.